Concentrating membrane proteins using ultrafiltration without concentrating detergents. Issue 10 (28th March 2016) - Feroz, Hasin; Vandervelden, Craig; Ikwuagwu, Bon; Ferlez, Bryan; Baker, Carol S.; Lugar, Daniel J.; Grzelakowski, Mariusz; Golbeck, John H.; Zydney, Andrew L.; Kumar, Manish
ABSTRACT: Membrane proteins (MPs) are of rapidly growing interest in the design of pharmaceutical products, novel sensors, and synthetic membranes. Ultrafiltration (UF) using commercially available centrifugal concentrators is typically employed for laboratory‐scale concentration of low‐yield MPs, but its use is accompanied by a concomitant increase in concentration of detergent micelles. We present a detailed analysis of the hydrodynamic processes that control detergent passage during ultrafiltration of MPs and propose methods to optimize detergent passage during protein concentration in larger‐scale membrane processes. Experiments were conducted using nonionic detergents, octyl‐β‐D glucoside (OG), and decyl‐β‐D maltoside (DM) with the bacterial water channel protein, Aquaporin Z (AqpZ) and the light driven chloride pump, halorhodopsin (HR), respectively. The observed sieving coefficient ( So ), a measure of detergent passage, was evaluated in both stirred cell and centrifugal systems. So for DM and OG increased with increasing filtrate flux and decreasing shear rates in the stirred cell, that is, with increasing concentration polarization (CP). Similar effects were observed during filtration of MP‐detergent (MPD) micelles. However, lower transmission was observed in the centrifugal system for both detergent and MPD systems. This is attributed to free convection‐induced shear and hence reduced CP along the membrane surface during centrifugal UF. Thus to concentrate MPs without retention of detergent, design of UF systems that promote CP is required. Biotechnol. Bioeng. 2016;113: 2122–2130. © 2016 Wiley Periodicals, Inc. Abstract : Membrane proteins (MPs) have hydrophobic exteriors that necessitate their stabilization into amphipathic detergent micelles. Concentrating low yield MPs using ultrafiltration often leads to concomitant concentration of detergent molecules. This excess detergent can have detrimental effects on MP activity and complicate downstream MP processing. The authors propose promoting concentration polarization (CP) to optimize detergent passage during protein concentration. This CP‐based approach completely contradicts current soluble protein concentration systems, including centrifugal filters, which are designed to maximize flux by minimizing CP.